2007
DOI: 10.1038/sj.gene.6364419
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of genetic studies in rodent models of autoimmune arthritis to understanding and treatment of rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic and potentially debilitating autoimmune disease. While novel therapies have emerged in recent years, disease remission is rarely achieved. RA is a complex trait, and the identifying of its susceptibility and severity genes has been anticipated to generate new targets for therapeutic intervention. However, finding those genes and understanding their function has been a challenging task. Studies in rodent intercrosses and congenics generated from inbred strains have been an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 124 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…The studies reported here employed rat PIA since this T-cell dependent disease model mimics human RA, including symmetrical involvement of peripheral joints, destruction of cartilage and bone, dysregulated pro-inflammatory cytokines/chemokines, rheumatoid factor positivity, and its chronic course. PIA is dependent on MHC class II-restricted T-cells [ 26 ] and influenced by non-MHC genes, producing cellular and humoral autoimmunity [ 16 , 25 , 41 ]. Non-MHC genes that influence rat PIA arthritis severity include TNFα, IL-1β [ 42 ], IL-6, IL-17 [ 43 ], and CCL-2, and joint damaging MMPs [ 25 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The studies reported here employed rat PIA since this T-cell dependent disease model mimics human RA, including symmetrical involvement of peripheral joints, destruction of cartilage and bone, dysregulated pro-inflammatory cytokines/chemokines, rheumatoid factor positivity, and its chronic course. PIA is dependent on MHC class II-restricted T-cells [ 26 ] and influenced by non-MHC genes, producing cellular and humoral autoimmunity [ 16 , 25 , 41 ]. Non-MHC genes that influence rat PIA arthritis severity include TNFα, IL-1β [ 42 ], IL-6, IL-17 [ 43 ], and CCL-2, and joint damaging MMPs [ 25 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is conceivable that some risk genes may interact with sex‐specific factors. They may also be specific for a single phenotype, and “susceptibility” genes may be less relevant than “severity” genes concerning the persistence of arthritis and joint‐destructive processes (14). We investigated whether APLEC influences autoimmunity in arthritis induced by rat type II collagen (CII), whether the genetic impact of APLEC is related to the way arthritis is triggered (i.e., to different types of arthritis), whether APLEC influences disease phenotypes other than susceptibility, and, finally, whether sex plays a role.…”
mentioning
confidence: 99%
“…The fibroblast-like synoviocyte (FLS) has a central role in the formation of the RA synovial pannus [5], and the in vitro invasive properties of FLS correlate with radiographic and histologic damage in RA [6] and in animal models of arthritis such as pristane-induced arthritis (PIA) [7]. Therefore, understanding the regulation of the invasive properties of FLS has the potential to generate new therapies aimed at reducing articular damage [8, 9]. …”
Section: Introductionmentioning
confidence: 99%